Anti-inflammatory and anti-apoptotic effects of the combination of Ligusticum chuanxiong and Radix Paeoniae against focal cerebral ischaemia via TLR4/MyD88/MAPK/NF-κB signalling pathway in MCAO rats. (28th November 2017) - Gu, Junfei; Su, Shulan; Guo, Jianming; Zhu, Yue; Zhao, Ming; Duan, Jin-ao
Abstract: Objective: This study was performed to assess the anti-inflammatory and anti-apoptotic effects of the combination of Ligusticum chuanxiong and Radix Paeoniae (XS) on focal cerebral ischaemic stroke. Methods: MCAO rats were used to evaluate the effect of XS on stroke. Cerebral water content was measured, and the levels of IFN-γ, IL-1β, IL-6 and IL-12 in serum and brain were assessed by ELISA kits. Protein expressions including p-p38, p-38, TLR-4, p-ERK, ERK, TLR-5, NF-κBp65, Myd88, Caspase-3 and Caspase-12 were examined by WB and IHC. Q-PCR was applied to examine IL-1β and IL-6 mRNA levels in the rat brain of each group. Key findings: XS treatment remarkedly decreased the levels of IFN-γ, IL-1β, IL-6 and IL-12 in serum and brain tissues of MCAO rats. In the ischaemic brain, the expressions of TLR-4, TLR-5, p-p38, p-ERK, Myd88, NF-κBp65, Caspase-3 and Caspase-12 were increased significantly, while the treatment attenuated the activated expressions by MCAO. XS also downregulated Caspase-3 and Caspase-12 expressions. IL-1β and IL-6 mRNA levels in MCAO brain tissue were decreased by XS treatment. Conclusions: XS could protect MCAO rats by anti-inflammation and anti-apoptosis through TLR4/MyD88/MAPK/NF-κB signalling pathway. Furthermore, the combination has a more meaningful improvement on focal cerebral ischaemic stroke.